Assessing the Performance of the Gsimcli Homogenisation Method with Precipitation Monthly Data from the COST-HOME Benchmark - Ribeiro, Sara (2022)
Ribeiro, S., Caineta, J., & Costa, A. C. (2017). Assessing the Performance of the Gsimcli Homogenisation Method with Precipitation Monthly Data from the COST-HOME Benchmark. In J. J. Gómez-Hernández, J. Rodrigo-Ilarri, E. Cassiraga, M. E. Rodrigo-Clavero, & J. A. Vargas-Guzmán (Eds.), Geostatistics Valencia 2016 (pp. 909-918). (Quantitative Geology and Geostatistics; Vol. 16). Springer. DOI: 10.1007/978-3-319-46819-8_63 ----------------------------- The authors gratefully acknowledge the financial support of Fundação para a Ciência e Tecnologia (FCT), Portugal, through the research project PTDC/GEO-MET/4026/2012 (“GSIMCLI – Geostatistical simulation with local distributions for the homogenization and interpolation of climate data”).